GAMBARAN STATUS KESEHATAN GIGI DAN MULUT PADA ANAK JALANAN DI KOTA BANDUNG - Neng Syifa Syariatilah; Sri Mulyanti; Isa Insanuddin; Irwan Supriyanto (Jurnal Kesehatan Siliwangi, 2020)
Street children are children who spend most of his time on the streets to work, play or activities of another. Street children live in the streets because of the dumped or get dumped from the family who is not able to bear the burden because of poverty, most of the time spent on the streets, so to pay attention to the health of the teeth and mouth are very limited. This research aims to know the description of the status of the health of the teeth and the mouth on the street children in Bandung. This type of research is descriptive research. The study population was all street children in Bandung. The research sample was taken by purposive sampling technique with a total sample of 16 people. After that, the resulting data processed and presented in the form of frequency distribution tables. The results showed that the average Index of oral hygiene on street children in Bandung City has the criteria of OHI-S bad (56,25%), The DMF-T on street children Bandung has averaged 7.4 DMF-T with very high criteria, meaning that each child of the streets, with an average of 7-8 caries on teeth permanent.